2022
DOI: 10.3168/jds.2021-20543
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary rumen-protected trans-10,cis-12 conjugated linoleic acid or a milk fat-depressing diet on energy metabolism, inflammation, and oxidative stress of dairy cows in early lactation

Abstract: The objective of this study was to determine the effects of milk fat depression induced by supplementing conjugated linoleic acid (CLA; trans-10,cis-12 and cis-9,trans-11 CLA) or feeding a higher starch and oilcontaining diet (HSO) on metabolic changes in dairy cows after calving. The main hypothesis was that the 2 strategies to decrease milk fat yield could have different effects on performance, energy balance (EB), and inflammatory status in early lactation. Thirty-three Nordic Red dairy cows were used in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Thus, the anti-obesity effects can be long-lasting. Studies carried out in dairy cows showed that the inclusion of CLA in the diet did not affect food consumption [25,26], which may be lower in the maintenance of the animals weight throughout the life cycle time. Although the potential of CLA to AID in weight .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, the anti-obesity effects can be long-lasting. Studies carried out in dairy cows showed that the inclusion of CLA in the diet did not affect food consumption [25,26], which may be lower in the maintenance of the animals weight throughout the life cycle time. Although the potential of CLA to AID in weight .…”
Section: Discussionmentioning
confidence: 96%
“…Thus, the anti-obesity effects can be long-lasting. Studies carried out in dairy cows showed that the inclusion of CLA in the diet did not affect food consumption [25, 26], which may be lower in the maintenance of the animals weight throughout the life cycle time. Although the potential of CLA to AID in weight loss is publicized, Vaisar et al [27] and Gaullier et al [28] indicate that in healthy individuals, this loss is less pronounced than in those who already have obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the anti-obesity effects can be long-lasting. Studies carried out in dairy cows showed that the inclusion of CLA in the diet did not affect food consumption ( Bayat et al, 2022 ; Castañeda-Gutierrez et al, 2007 ), which may be lower in the maintenance of the animals weight throughout the life cycle time. Although the potential of CLA to AID in weight loss is publicized, Vaisar et al (2022) and Gaullier et al, (2004) indicate that in healthy individuals, this loss is less pronounced than in those who already have obesity.…”
Section: Discussionmentioning
confidence: 98%
“…Feeding strategies can be used to modify milk yield and composition as lipid supplementation [11,12]. Rumen-protected fats from different sources have been used to improve physiological responses, milk yield, and composition in ruminants [10,13]. Protecting fat from ruminal biohydrogenation determines the efficiency of FAs transferred into milk and the percentage of n-3 FA improvements in milk [4].…”
Section: Introductionmentioning
confidence: 99%